Differences in intestinal microflora of birds among different ecological types - Wang, Jia; Hong, Mingsheng; Long, Juejie; Yin, Yanqiang; Xie, Jianmei (Frontiers in Ecology and Evolution, 2022)
The intestinal microflora of animals plays a key role in metabolism, immunity, and development. Birds distributed across multiple ecological habitats. However, little is known about the differences in the intestinal microflora of birds among different ecological types. In this study, bird faeces from different ecological types and orders were collected in Chongqing Zoo, China. In this study, high throughput sequencing of the 16S ribosomal RNA (rRNA) gene (amplicon sequencing) and metagenomics were used to analyze the composition and function differences of gut microbiota communities among different ecological types/orders. Firmicutes and Proteobacteria were the dominant bacteria phyla for all samples but there were significant differences in the α-diversity, community structure and microbial interactions between birds of different ecological types. The function differences involve most aspects of the body functions, especially for environmental information processing, organismal systems, human diseases, genetic information processing, and metabolism. These results suggest that diet and habitat are potential drivers of avian gut microbial aggregation. This preliminary study is of great significance for further research on the intestinal microflora of different ecological types of birds.